Inventory Information System at PT. Jaya Tegar Sejahtera Uses the FIFO Method in the Production Process - Kusmanto, Tria Hadi (Yayasan Mitra Peduli Indonesia, 2024)
Action research focuses on product identification and management to collect data on available commodity inventory, also called inventory systems. The author's focus in this context is on PT. Jaya Tegar Sejahtera at this time. The greater the complexity of data management related to stock availability, including shortages, excess stock, and stock level variations, the more goods PT. Jaya Tegar Sejahtera has in stock. Realizing that the business is growing and more data needs to be processed, PT. Jaya Tegar Sejahtera requires a software application to conduct inventory. Therefore, PT. Jaya Tegar Sejahtera needs an inventory information system to help with all inventory management tasks and determine the amount of inventory needed to meet all client requests. The study aims to create an inventory information system that follows the First In, First Out (FIFO) method to overcome existing problems using MySQL and PHP. The results of this study indicate that this inventory information system can make it easier for the sales department to request goods, allow companies to check directly into the warehouse to find stock information and help users work more productively and effectively in inventory management.